The case of the missing books : a mobile library mystery - Sansom, Ian. (New York : Harper, 2006)
Israel Armstrong, a new Emerald Isle bookmobile attendant, discovers that the roving library's 15,000 books have disappeared and that he cannot resign from his job until he finds them.
Keywords: Jews -- Ireland -- Fiction; Librarians -- Ireland -- Fiction; Traveling libraries -- Ireland -- Fiction; Theft -- Fiction; Mystery fiction